Studies on Air-layering on Blue Pine (Pinus wallichiana A.B.Jackson) - Chandra, J. P. (Indian Forester, 1974)
Results of a trial conducted on air-layering of blue pine branches are reported. Application of Seradix B3 induced rooting in 30 per cent of air-layers while air-layers wlthout the application of Seradix did not root.